2017
DOI: 10.1177/0193945917747416
|View full text |Cite
|
Sign up to set email alerts
|

Safety Culture, Patient Safety, and Quality of Care Outcomes: A Literature Review

Abstract: This integrative literature review was conducted to examine the relationships between safety culture and patient safety and quality of care outcomes in hospital settings and to identify directions for future research. Using a search of six electronic databases, 17 studies that met the study criteria were selected for review. This review revealed semantic inconsistencies, infrequent use of a theory or theoretical framework, limited discussions of validity of instruments used, and significant methodological vari… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

5
103
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2
1

Relationship

1
8

Authors

Journals

citations
Cited by 118 publications
(114 citation statements)
references
References 44 publications
5
103
1
5
Order By: Relevance
“…Overall, positive organisational culture influences various elements of organisational behaviour, including healthcare quality and safety (Braithwaite, Herkes, Ludlow, Testa, & Lamprell, ; DiCuccio, ; Jacobs et al, ; Lee et al, ; Taylor, Clay‐Williams, Hogden, Braithwaite, & Groene, ). Implementation of PSC improves clinical practices; for example, the introduction of PSC has been linked to reductions in adverse events/errors (El‐Jardali, Dimassi, Jamal, Jaafar, & Hemadeh, ; Mardon, Khanna, Sorra, Dyer, & Famolaro, ; Robb & Seddon, ; Singer et al, ; Wang et al, ) and an improvement in certain clinician behaviours such as error reporting (Verbakel, Langelaan, Verheij, Wagner, & Zwart, ).…”
Section: Introductionmentioning
confidence: 99%
“…Overall, positive organisational culture influences various elements of organisational behaviour, including healthcare quality and safety (Braithwaite, Herkes, Ludlow, Testa, & Lamprell, ; DiCuccio, ; Jacobs et al, ; Lee et al, ; Taylor, Clay‐Williams, Hogden, Braithwaite, & Groene, ). Implementation of PSC improves clinical practices; for example, the introduction of PSC has been linked to reductions in adverse events/errors (El‐Jardali, Dimassi, Jamal, Jaafar, & Hemadeh, ; Mardon, Khanna, Sorra, Dyer, & Famolaro, ; Robb & Seddon, ; Singer et al, ; Wang et al, ) and an improvement in certain clinician behaviours such as error reporting (Verbakel, Langelaan, Verheij, Wagner, & Zwart, ).…”
Section: Introductionmentioning
confidence: 99%
“…A comprehensive view of safety culture comprises both occupational and patient safety culture. Most studies, however, observed occupational and patient safety culture separately [for occupational safety culture see, e.g., [ 2 , 3 ] and for patient safety culture, e.g., [ 4 , 5 , 6 , 7 , 8 , 9 ]. Recently, several studies were conducted that included both constructs [ 10 , 11 , 12 , 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%
“…There has been fairly extensive research into the effects of safety culture on patient safety in healthcare organizations internationally, but these effects are not yet clearly understood. To improve understanding of the relationships it has been recommended that researchers consider using a theoretical framework and give more attention to the use of valid measures and appropriate analytic approaches (Groves, 2014; Lee et al, 2019).…”
mentioning
confidence: 99%
“…Among the five studies we identified that investigated the perspectives of healthcare professionals on safety culture and overall patient safety in various countries (Alswat et al, 2017; Ammouri et al, 2015; El‐Jardali et al, 2011; Saleh et al, 2015; Wang & Tao, 2017), only one used multilevel modeling (i.e., Wang & Tao, 2017), although they all drew participants from multiple hospitals. Similarly, a review of 17 international studies of safety culture and patient safety outcomes found great variation in the level of analysis, with data analyzed at the individual level in five studies, at the unit level in five studies, at both the individual and unit levels in three studies, and at the hospital level in four studies (Lee et al, 2019). Thus, too few studies of safety culture have employed multilevel modeling.…”
mentioning
confidence: 99%